Penerapan Metode Dzikrulloh dalam Mengembangkan Akhlaqul Karimah Anak Didik Ponpes TQN Suryalaya Surabaya - Muchamad Suradji; Endro Priyantono; Sampiril Taurus Tamaji (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
This article is the result of qualitative research, which explains the meaning of the Dzikrulloh method and its application in developing the Akhlaqul Karimah of students at TQN Suryalaya Islamic Boarding School, Surabaya. The research data were obtained from several data collection instruments, including observation, interviews, documentation, and questionnaires which revealed the application of the Dzikrulloh method in developing good morals. Then the research data were analyzed using descriptive analytical techniques. Based on the results of the study, it was concluded that in the application of the Dzikrulloh method in developing Akhlaqul Karimah for students at TQN Suryalaya Islamic Boarding School Surabaya, the teacher must adjust the material being taught and the learning atmosphere, considering that learning takes place in the last hour which makes students experience saturation and boredom. The Dzikrulloh method is a strategy that makes students not feel bored and become more active to increase student learning outcomes in the akhlaqul karimah subject to be more improved than before. The teacher's efforts in implementing the Dzikrulloh Method at the TQN Suryalaya Islamic Boarding School include; encouraging student motivation, creating variations in-class learning, serving student differences, increase student interaction.